2016
DOI: 10.1371/journal.pone.0148059
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy-Free Pulmonary Vein Isolation in Patients with Atrial Fibrillation and a Patent Foramen Ovale Using Solely an Electroanatomic Mapping System

Abstract: IntroductionThe advent of electroanatomical mapping (EAM) systems for pulmonary vein isolation (PVI) has dramatically decreased radiation exposure. However, the need for some fluoroscopy remains for obtaining left atrial (LA) access. The aim was to test the feasibility of fluoroscopy-free PVI in patients with atrial fibrillation (AF) and a patent foramen ovale (PFO) guided solely by an EAM system.MethodsConsecutive patients with AF undergoing PVI and documented PFO were studied. An EAM-guided approach without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Second, in this small group of patients, there were no significant complications, though the technique should be validated and refined in larger cohorts in the future. Additionally, the TSP fluoroscopy times in this small group of patients were higher than previously reported values; 5,9,10,12 this may be due to the assistance of general cardiology fellows, who generally require longer fluoroscopy times for TSP than an experienced cardiologist, and the addition of patients with either paroxysmal or persistent AF, the latter of which may require longer procedure times and fluoroscopy use.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Second, in this small group of patients, there were no significant complications, though the technique should be validated and refined in larger cohorts in the future. Additionally, the TSP fluoroscopy times in this small group of patients were higher than previously reported values; 5,9,10,12 this may be due to the assistance of general cardiology fellows, who generally require longer fluoroscopy times for TSP than an experienced cardiologist, and the addition of patients with either paroxysmal or persistent AF, the latter of which may require longer procedure times and fluoroscopy use.…”
Section: Discussioncontrasting
confidence: 56%
“…4–7,913,1519 Kühne et al advocate using transesophageal echocardiography (TEE) prior to TSP access, 10 whereas several groups describe intra-procedural TEE-guided TSP access with a high degree (97–100%) of AF-free event rates during respective follow-up periods. 13,16,17 Other groups have described TEE-guided TSP in combination with fluoroscopy to minimise radiation exposure, however reported outcomes from this approach demonstrated comparatively reduced AF-free success rates (75–85%).…”
Section: Discussionmentioning
confidence: 99%
“…Kuhne et al. described a case series in which nonfluoroscopic LA access was obtained through the patent foramen ovale . We did not use this approach for our patients, even if they had a foramen ovale, because its cranial and anterior locations compromise the catheter contact and stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns about the safety of this approach have been raised. A few single‐center studies with relatively small cohorts have shown that the zero‐fluoroscopy approach using 3D mapping systems, ICE, and computed tomography (CT) imaging integration does not compromise the safety and efficacy of PV isolation (PVI) . The aim of this multicenter study was to assess the safety and clinical efficacy of nonfluoroscopic radiofrequency (RF) catheter ablation without CT or magnetic resonance imaging (MRI) integration and without using contrast media for the treatment of AF in a large cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have shown feasibility of fluoroscopy-free pulmonary vein isolation in 26 out of 30 consecutive patients with a documented PFO [15]. Bulava et al [16] demonstrated the feasibility of zero fluoroscopy ablation in 40 patients with paroxysmal AF using ICE imaging and three-dimensional EAM mapping with contact force measurements.…”
Section: Discussionmentioning
confidence: 99%